The Necessity of Monitoring Pesticide Residues in Vegetables and Fruits Using Hazard Index among Consumers - Reza SHOKOOHI; Mohammad Taghi SAMADI; Manoochehr KARAMI; Razieh KHAMUTIAN (Tehran University of Medical Sciences, 2019)
The Necessity of Monitoring Pesticide Residues in Vegetables and Fruits Using Hazard Index among Consumers